Solid Waste Management, Challenges and Possible Sustainable Solutions - Shrivastava, Akrati; Ravichandran, S. (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2023)
The undesirable or worthless solid materials produced by human activity in residential, commercial, or industrial locations are referred to as solid waste. It is made up of a vast range of types of both biological and inorganic substances. These materials is classified on the basis of types of material such plastic, paper, metal organic waste, glass, toxic non-toxic flammable radioactive elements, industrial waste, domestic waste etc. The only factors contributing to the high and rising rate of solid waste generation are urbanisation and population increase, and managing this waste properly is a significant issue. We have to tackle this issue now otherwise; it may create hazardous and incurable problems. There is widespread problem in many developing and developed countries in the world regarding disposal waste material. Because of increase in population, industrialization wastes are generated in societies. About 7.6 million tons of wastes have been produced worldwide and out of which 9-13% of which have been recycled. The creation of waste, as well as its storage, collection, transportation, processing, and disposal, are all included in solid waste management. Ineffective solid waste management has a negative influence on citizens’ quality of life, accelerates the depletion of natural resources, pollutes the environment, and deteriorates public health. The only factors contributing to the high and rising rate of solid waste generation are urbanisation and population increase, and each city’s municipal corporation faces significant challenges in properly managing this waste. Household solid waste poses a significant risk to health and facilitates the spread of infectious diseases. In order to safeguard public health, the environment, and natural resources, solid waste management is an issue that needs to be handled correctly. This article focused on the sources and constituents of solid waste, the kind and volume of trash disposed of, disposal techniques, and the effects of solid waste on health. It also provides an overview of the importance of solid waste management, the challenges it faces and potential sustainable solutions.